Risk management, the subprime crisis and finance-dominated capitalism: what went wrong? A systematic literature review - Lagoa, S.; Leão, E.; Barradas, R. (The demise of finance-dominated capitalism explaining the financial and economic crises, 2015)
Over time the financial sector has gained greater relevance in the economy, a phenomenon that some call financialisation or finance-dominated capitalism. Contrary to the mainstream view, financialisation literature emphasises that risk management by financial corporations will not be socially efficient in a context of deregulated markets and will ultimately lead to an increase of aggregate risk and crises. To assess the validity of such claim, in this paper we review the literature on risk management during the Subprime crisis. These failures fall into three categories: technique and methodology, corporate governance and strategy, and regulation and external factors. We conclude that these failures can be interpreted in the light of the financialisation perspective, which is therefore a valuable approach when addressing regulatory changes in the financial system.